Phase transitions in Al 3Ca 8 and Al 14Ca 13 intermetallic compounds induced by milling and annealing - Chaubey A.K.; Scudino S.; Prashanth K.G.; Stoica M.; Vaughan G.; Mukhopadhyay N.K.; Mishra B.K.; Eckert J. (My University, 2025)
The phase transformations occurring in mechanically milled and annealed triclinic Al 3Ca 8 intermetallic compound have been studied. The Al 3Ca 8 phase transforms initially to the nanostructured monoclinic Al 14Ca 13 intermetallic during milling. The Al 14Ca 13 phase is metastable and transforms back to the Al 3Ca 8 compound during subsequent heating. The transformation starts at low temperature with the grain coarsening of the Al 14Ca 13 phase. At intermediate temperatures, the transformation from Al 14Ca 13 to Al 3Ca 8 occurs. The sequence is completed at high temperatures with the grain coarsening of the Al 3Ca 8 phase. © 2012 Elsevier B.V. All rights reserved.